Exploring the Non-Toxic Therapeutic Potential of Dioscorea communis in Combating Oral Pathogenic Bacteria and Their Effects on Hard and Soft Oral Tissues - Anastasia-Ioanna Papantonaki; Eleni Georgakopoulou; Christina Barda; Panagiota Loumou; Ioannis Sfiniadakis; Jane Anastassopoulou; Andreas Vitsos; Michail Christou Rallis (Biomedicines)
Background/Objectives: Gingivitis and dental caries are oral diseases resulting from bacterial accumulation in dental plaque, leading to inflammation, tissue destruction and the demineralization of tooth structures. Dioscorea communis, due to its anti-inflammatory and antimicrobial properties, could be a new treatment candidate. Methods: This study evaluated the preventive and therapeutic effect of a D. communis berry juice paste, formulated at 3% and 7% concentrations, on gingivitis and dental caries, in 55 male SKH-hr2 hairless mice. Gingivitis and dental caries were induced by ligation of the upper left incisor and the paste was applied topically three times daily, five days a week. Treatment efficacy was assessed through clinical examinations, photo-documentation, histopathological analysis and FT-IR spectroscopy. Results/Conclusions: Preventive administration of D. communis 7% significantly delayed disease onset, while therapeutic effects on established conditions were limited. Both concentrations were non-toxic to gingival tissues and dental structures.